Keris Kamardikan Surakarta - Febrian Wisnu Adi (Ars: Jurnal Seni Rupa dan Desain, 2011)
The aim of this research is to be searched about aesthetic and historical background that includes the shape, meaning, and function as well as the factors that underlie keris kamardikan in Surakarta. The analysis of the keris kamardikan Surakarta is not a simple matter.  The question such as: what keris kamardikan is; why it had been created; when it start created; whose the man behind of created; where place that keris kamardikan has been exsist; and how about the histocal about it. Change of palace culture maybe happen to the progresive culture with any perception. It can be indicated like social criticism movement in postmodern age, such as: happening art, environmental art, etc. While the factors underlie the similarities and differences are the internal and external factors. The Internal factors are the rules and policy stated by the actor in this regions. The external factor is the factor happens because the society social condition that is more developed as well as the policy of the government of Republic of Indonesia in the tourism sector. The method used in the research is qualitative research with multidicipline approach focusing on the study of art. Aesthetic approach is used for relating the style of art.  This approach is used with other approaches and use the relevant teories such as: history, communication, anthropology, archeology, and sociology. This research has conelude that movemen of keris kamardikan Surakarta is in the structure or style. Historical background of movement started on 1970 in case of many keris artist in Surakarta created it with many purposed, basicly keris Kamardikan Surakarta have two poin of movement, there are an aesthetic and historical.Keyword: keris, kamardikan, Surakarta, aesthetic, and history.